STUDENTS LANGUAGE ANXIETY THROUGH MEMORIZATION: AN ANALYSIS OF PERFORMANCE AND BEHAVIOR IN A SPEAKING - Asnawati, Asnawati (Teaching English as a Foreign Language Overseas Journal, 2022)
The objectives of the research were (1) to know the students speaking performance through memorization influence student’s language anxiety and (2) to know the student’s speaking behaviors through memorization influence student’s language anxiety. The researcher applied quasi-experimental method. There were two classes namely control and experimental group. The Population of this research were students at SMPN 22 Mesuji which consisted of 270 students. The sampling technique in this research was random sampling. The researcher chose sample by selecting the sample and took two classes from second grade at SMPN 22 Mesuji. The classes consisted of 20 students. So, the total samples of this research were 40 students. The research data were collected using test, questionnaire and analyzed by means descriptive statistic through SPSS version 16 for windows program.  The result of this research showed that (1) the students speaking performance through memorization influence student’s language anxiety. (2) the student’s speaking behaviors through memorization influence student’s language anxiety